Das traumatisierte Subjekt: Geschlecht – Körper – Soziale Praxis. Eine gendertheoretische Begründung der Soma Studies - Wuttig, Bettina (transcript, 2016)
How is a (gendered) subject created out of a human being? Bettina Wuttig carries out the investigation into the materialization of gender through a trauma discourse inflected by Cultural Studies. Via a power-critical reading of neuroscientific theories of memory, and with reference to Judith Butler, Friedrich Nietzsche and Gilles Deleuze, (bodily) resistant perspectives are opened up, which make (gendered) subjectivizations visible as somatic practices of injury and memory. The study provides important impetus to Soma Studies – a system of thought that analyzes the material body in relation to social practices at the intersections between the humanities and critical life-scientific epistemology.